Complete mitochondrial genome of Chironomus nipponensis, new record from China (Diptera: Chironomidae). Issue 6 (3rd June 2022) - Shen, Mi; Li, Yufei; Yao, Yuping; Fu, Yue
Abstract: The complete mitochondrial genome of Chironomus nipponensis Tokunaga, 1936 was sequenced and assembled from the whole genome data. The mitochondrial genome length was 16184 bp and contained 22 transfer RNA genes, 13 protein-coding genes, 2 ribosomal RNA genes, and 1 D-loop control region. Phylogenetic and taxonomic analysis based on the concatenated nucleotide sequences of 37 genes from 14 related species was reconstructed. The phylogeny revealed that C. nipponensis is closely related to three other Chironomus species, which is consistent with the traditional morphological studies.